Ethnographie matérielle, sonore et spatiale de la mort en pays maale (Éthiopie méridionale) - Hugo Ferran (Afriques)
The Maale of southwestern Ethiopia tell two categories of deceased persons apart. The first, without descendants, die “fully” since the group evacuates them from memory, whereas the second, who have descendants, die “partially” since they acquire the status of ancestors following three rituals after their death. Although ancestors are burried in the elder son’s household, only the most prestigious among them still live on in the group’s memory. Two systems for remembering ancestors and “big men” are analyzed: the one material (the spatial arrangements of graves in households), the other immaterial (the music performed during funeral ceremonies). Examining the basis of the group’s memory reveals that the so-called traditional social organization is based on both an “inegalitarian” system, which tends to situate human beings by their lineage rank, and an “egalitarian” system, which seeks to raise a person’s status by emphasizing success (wealth, fertility, feats of war or hunting, etc.).